“I Mainly Rely on the Textbook:” a call for teacher enhancement in agricultural sciences - Baas, Nkwenyana Solomon; Tsotetsi, Cias Thapelo (OpenED Network, 2023)
Universities play a crucial role in teachers' professional development. This study aims to examine the following research question: How can universities enhance the teaching of agricultural sciences in schools? Previous research has focused on the university’s collaboration with stakeholders, such as parents, to enhance teaching, but without a specific focus on the teaching of agricultural sciences. In response to this question, a transformative theoretical framework anchors this study. This study employed a participatory action research design involving focus group discussions to determine the need for improving the teaching of agricultural sciences. Eleven participants were involved in this research, and pseudonyms were used to ensure privacy and protect their identities. The study findings from the three schools in the Thabo Mofutsanyana District of the Free State Province, included in the study, revealed that there is an inability to meet curriculum requirements, accompanied by a reluctance to implement continuous professional teacher development. The findings emphasize the need for extended university involvement in the implementation of teacher development policies to address the teachers’ needs.
Keywords: Agricultural sciences; Participatory action research; Continuous professional teacher development; Curriculum and policy assessment; Policy statement